Photocatalytic composite membrane material as well as preparation method and application thereof
By using photocatalytic composite film materials in membrane technology, including base films, bridge layers and β-FeOOH nanorods prepared by 3D printing, the problems of low oil-water separation efficiency and insufficient chemical stability in the existing membrane technology are solved, and efficient oil-water separation and good cycle stability are achieved.
Patent Information
- Application Number
- CN202510071382.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-18
AI Technical Summary
The existing membrane technology has problems such as membrane pollution, low separation efficiency and insufficient chemical stability during oil-water separation, which limits its application scope.
A photocatalytic composite film material is used, which includes a base film (acrylonitrile-butadiene-styrene copolymer), a bridge layer (polymer containing sulfonic acid groups) and a β-FeOOH nanorod. The base film is prepared by 3D printing and a bridge layer and nanorod are formed on its surface to improve the surface roughness and hydrophilicity of the film.
Good water flux and oil-water separation efficiency are achieved, and the membrane is given photocatalytic decomposition ability, improving pollution resistance and circulation stability.
Smart Images

Figure CN119838453A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of separation membrane technology, and in particular to a photocatalytic composite membrane material and a preparation method and application thereof. Background Art
[0002] Membrane technology has become the most widely used technology for oil-water separation due to its advantages such as high separation efficiency, low cost and no secondary pollution. However, membrane fouling and membrane separation efficiency are still huge challenges restricting the application of membranes. Summary of the invention
[0003] In view of the above problems, the present application provides a photocatalytic composite membrane material and a preparation method and application thereof. The composite membrane material provided in the present application has the advantage of good cycle stability.
[0004] In one aspect, the present application provides a photocatalytic composite film material, comprising:
[0005] Base film: comprising acrylonitrile-butadiene-styrene copolymer;
[0006] A bridging layer is located on one side of the base film; the bridging layer includes a polymer, and the polymer includes a sulfonic acid group;
[0007] β-FeOOH nanorods: located on a surface of the bridging layer facing away from the base film, and the β-FeOOH nanorods are connected to the sulfonic acid groups.
[0008] In some embodiments, based on the total mass of the bridging layer, the mass percentage of the sulfonic acid group is 3.5% to 8.5%.
[0009] In some embodiments, based on the total mass of the bridging layer, the mass percentage of the β-FeOOH nanorods is 1.5% to 11.5%.
[0010] In some embodiments, the polymer includes structural units derived from 2-acrylamide-2-methylpropane sulfonic acid or a salt thereof monomer;
[0011] In some embodiments, the weight average molecular weight of the polymer is 300 to 100,000.
[0012] In some embodiments, the aspect ratio of the β-FeOOH nanorods is 40 to 60:1.
[0013] In some embodiments, the BET specific surface area of the β-FeOOH nanorods is 75 m 2 / g~105m 2 / g. In some embodiments, the base film is made by 3D printing;
[0014] The base film has a porous structure, and the average pore size of the porous structure is 100 μm to 400 μm;
[0015] The average pore height of the porous structure is 100 μm to 500 μm.
[0016] The second aspect of the present application is to provide a method for preparing the composite membrane material according to the first aspect, comprising the following preparation process:
[0017] Providing a base film: the base film is prepared by a melt deposition method in 3D printing;
[0018] The base film is subjected to surface treatment to obtain a treated base film;
[0019] placing the treated base film in a monomer solution containing sulfonic acid groups to react to obtain a base film containing a bridging layer;
[0020] The base film including the bridging layer is placed in an iron precursor solution, and β-FeOOH nanorods are generated on a surface of the bridging layer that is away from the base film.
[0021] In some embodiments, the step of placing the treated base film in a monomer solution containing sulfonic acid groups for reaction comprises:
[0022] adding a monomer solution containing sulfonic acid groups to the irradiation tube;
[0023] placing the treated base film in a monomer solution containing sulfonic acid groups;
[0024] Deoxidation treatment for a period of time;
[0025] Radiation grafting is performed to prepare a base film including a bridging layer.
[0026] In some embodiments, the step of generating β-FeOOH nanorods comprises:
[0027] providing an iron precursor solution;
[0028] placing the base film including the bridging layer in the iron precursor solution;
[0029] The β-FeOOH nanorods are prepared by heating the reaction in a water bath, the water bath temperature is 50° C. to 80° C., and the water bath time is 12 h to 36 h.
[0030] In some embodiments, the step of surface treating the base film comprises:
[0031] Ultrasonic cleaning of the basement membrane to remove surface contaminants;
[0032] The base film is placed in an etching solution at 40°C to 80°C for 10min to 30min;
[0033] After the treatment is completed, take it out, wash it with deionized water, and then dry it.
[0034] The third aspect of the present application is to provide an application of a photocatalytic composite membrane material in the field of oil-water separation, wherein the composite membrane is the composite membrane material described in the first aspect or the composite membrane material prepared by the preparation method described in the second aspect.
[0035] Beneficial technical effects of this application:
[0036] (1) The composite membrane material provided in this application has good water flux.
[0037] (2) The composite membrane material provided in this application has good oil-water separation efficiency.
[0038] (3) The composite membrane material provided in the present application has photocatalytic decomposition capability, which further improves the anti-pollution ability of the membrane.
[0039] (4) The composite membrane material provided in this application has good cyclic stability.
[0040] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:
[0042] Figure 1A and Figure 1B The following is a process flow chart of preparing the composite membrane according to the embodiment of the present application;
[0043] FIG. 2A to FIG. 2E A scanning electron microscope image (SEM) of a composite membrane illustrated in an embodiment of the present application;
[0044] Figure 2F A scanning electron microscope image (SEM) of a composite membrane illustrated as a comparative example of the present application;
[0045] Figure 3A The water contact angle test diagram of the composite film shown in the examples and comparative examples of the present application;
[0046] Figure 3BIt is a test diagram of underwater oil contact angle of the composite membrane illustrated in the embodiments and comparative examples of the present application;
[0047] Figure 4A The water flux test diagram of the composite membrane shown in the examples and comparative examples of the present application;
[0048] FIG. 4B to FIG. 4F This is a test diagram of the separation efficiency of the composite membranes shown in the examples and comparative examples of the present application;
[0049] Figure 5 This is a graph showing the cyclic stability test of the composite membrane according to an embodiment of the present application;
[0050] Figure 6 This is a photo-Fenton catalytic test diagram of the composite membrane illustrated in the embodiment of the present application. DETAILED DESCRIPTION
[0051] Hereinafter, the photocatalytic composite film material of the present application, its preparation method and application implementation methods are specifically disclosed with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0052] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0053] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0054] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0055] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0056] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0057] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0058] If not otherwise specified, in this application, the terms "first", "second", etc. are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the quantity, specific order or primary and secondary relationship of the indicated technical features.
[0059] Unless otherwise specified, in this application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple sheets" refers to more than two sheets (including two sheets).
[0060] In recent years, due to the increasing demand for oil caused by the development of industrial production, oily pollutants in industrial wastewater have attracted widespread attention. So far, different technical solutions have been developed for oil-water separation and the recovery and utilization of leaked crude oil, such as gravity sedimentation, combustion, biodegradation and chemical coagulation. However, these methods generally have disadvantages such as high cost, low efficiency, and difficult operation, and may even cause secondary pollution. For example, the combustion method will produce carcinogenic gases and pollute the atmosphere. Therefore, it is urgent to develop efficient and simple methods to treat oil pollution.
[0061] Membrane separation is a popular technology widely used in the field of water treatment. Compared with other treatment methods, it has the advantages of simple operation, low energy consumption and high separation efficiency. It is considered to be one of the most competitive technologies used in the field of oil-water separation. However, membrane fouling problems and the trade-off effect between permeability and selectivity have always limited the application of membrane separation technology. At the same time, the limited chemical stability of the membrane under adverse conditions also affects the service life of the membrane. In addition, the exploration and implementation of innovative membrane technologies, such as 3D printed membranes, stimuli-responsive membranes and biomimetic membranes, have become the forefront of research. These advances mark the transformative potential for improving the scope and enhancing the application of membrane-based separation processes.
[0062] 3D printing technology can accurately design and control the macroscopic structure of the membrane through computers, such as cutting the membrane pore size, porosity and surface morphology with unparalleled precision, and also has the advantage of being able to achieve one-time membrane formation. 3D printing technology is mainly divided into four categories: photopolymerization, powder fusion, material extrusion and sheet lamination. Among them, fused deposition manufacturing (FDM) is widely used because of its low cost, simple operation and high speed. FDM technology extrude thermoplastic plastic filaments on a tray according to the coordinates preset by the software, and a membrane structure is formed after two layers of plastic filaments are stacked.
[0063] As a model material for 3D printing technology, acrylonitrile butadiene styrene (ABS) has the common properties of the three components and is a non-toxic material with good impact resistance, heat resistance, low temperature resistance, etc.
[0064] Therefore, compared with traditional commercial membranes, 3D printed membranes are not only tougher and more resistant to acid and alkali, but also have significantly reduced toxicity. 3D printed membranes bring new possibilities for the optimization of materials and structures of commercial membranes. However, 3D printed membranes cannot be used directly as separation membranes. For example, the hydrophobic characteristics of 3D printed ABS membranes themselves cause serious membrane contamination during the oil-water separation process.
[0065] As a semiconductor material, β-FeOOH has a small bandgap of only 2.1eV, high visible light response, small particle size and high specific surface area. However, β-FeOOH is often used as a powder catalyst, which is difficult to disperse and recycle, and sometimes inevitably produces secondary pollution. At the same time, powdered iron oxyhydroxide has the disadvantages of easy precipitation, poor water solubility, and difficulty in reuse, so it is difficult to load on the surface of fabrics. Therefore, adhering photocatalytic particles to the surface of fabrics has become a current research hotspot.
[0066] Therefore, the present application provides a photocatalytic composite film material, which includes a base film, the base film includes acrylonitrile-butadiene-styrene copolymer; a bridging layer located on one side surface of the above-mentioned base film, the bridging layer includes a polymer, and the polymer includes sulfonic acid groups; the composite film also includes β-FeOOH nanorods, and the β-FeOOH nanorods are connected to the above-mentioned sulfonic acid groups.
[0067] The base film of the present application is used as a support film, and the base film itself has low roughness and strong hydrophobicity, and β-FeOOH nanorods are not easily generated on its surface. The present application forms a bridging layer on the surface of the base film, which improves the surface roughness of the film. At the same time, the polymer of the bridging layer contains sulfonic acid groups, which further serve as a bridging agent to facilitate the combination with the β-FeOOH nanorods. Specifically, the β-FeOOH nanorods and the sulfonic acid groups contain chemical bonds and intermolecular forces, which makes the β-FeOOH nanorods have a strong binding ability on the membrane surface, enhances the interface bonding strength, and improves the structural stability of the membrane itself.
[0068] The present application uses a polymer containing sulfonic acid groups and β-FeOOH nanorods to modify the ABS-based membrane, thereby improving the surface hydrophilicity and anti-fouling properties of the membrane. Specifically, the water flux of the composite membrane material is increased, and the oil-water separation efficiency is increased. At the same time, the catalytic properties of β-FeOOH give the membrane photocatalytic decomposition ability, further improving the membrane's anti-fouling ability. Therefore, the composite membrane material provided by the present application also has the advantage of good cycle stability.
[0069] The composite membrane material provided in the present application has certain application prospects in the field of oil-water separation. For example, in the field of oily wastewater, the composite membrane material provided in the present application is further made into the required composite membrane assembly, and the composite membrane assembly is placed in an industrial membrane oily wastewater treatment device for treating oily wastewater.
[0070] The first aspect of the present application is to provide a photocatalytic composite film material, which includes a base film, the base film includes acrylonitrile-butadiene-styrene copolymer; a bridging layer located on one side surface of the above-mentioned base film, the bridging layer includes a polymer, and the polymer includes sulfonic acid groups; the composite film also includes β-FeOOH nanorods, and the β-FeOOH nanorods are connected to the above-mentioned sulfonic acid groups.
[0071] The base film of the present application is mainly used as a support film. When the material of the support film includes acrylonitrile-butadiene-styrene copolymer, the acrylonitrile-butadiene-styrene copolymer contains structural units derived from acrylonitrile monomers, structural units derived from butadiene monomers, and structural units derived from styrene copolymers; based on the total molar number of each monomer, the molar percentage content of the structural unit derived from the acrylonitrile monomer is 15% to 35%, the molar percentage content of the structural unit derived from the butadiene monomer is 5% to 30%, and the molar percentage content of the structural unit derived from the styrene copolymer is 40% to 60%.
[0072] The base film of the present application is prepared by a 3D printing method, which will be described in detail in the following embodiments.
[0073] The polymer of the present application refers to a collection of macromolecules that are chemically uniform but different in degree of polymerization, molar mass and chain length prepared by polymerization. The term also includes derivatives of such macromolecular collections formed by polymerization, i.e. compounds that can be obtained by reaction of functional groups in the above macromolecules, such as addition or substitution, and can be chemically uniform or chemically inhomogeneous.
[0074] The copolymer of the present application refers to a polymer formed by polymerization of two or more different monomers (monomers are the basic units that make up a polymer). Unlike homopolymers (polymerized from a single type of monomer), copolymers contain different types of repeating units (monomers) in their molecular chains.
[0075] The bridging layer of the present application plays a bridging role. This is because the base film itself has low roughness and strong hydrophobicity. The present application forms a bridging layer on the surface of the base film, which improves the surface roughness of the membrane and facilitates the attachment of β-FeOOH nanorods. At the same time, since the monomers forming the bridging layer contain hydrophilic functional groups, such as sulfonic acid groups, it is beneficial to further improve the hydrophilicity of the membrane, thereby increasing the water flux of the membrane.
[0076] The β-FeOOH (β-ferrite) of the present application is an inorganic nanomaterial with a special tunnel structure. It has a huge specific surface area and good adsorption performance, and can be used to remove pollutants in water. β-FeOOH also exhibits good catalytic activity in redox reactions, especially catalyzing H 2 O 2 Hydroxyl (·OH) free radicals are generated, thereby oxidizing and degrading the organic dye molecules in the oil-water mixture, and finally obtaining pollution-free inorganic substances.
[0077] Therefore, the composite membrane material provided in the present application has a high water flux and a high separation efficiency for oil-water mixtures. At the same time, the catalytic properties of β-FeOOH give the membrane photocatalytic decomposition ability, further improving the membrane's anti-pollution ability. Therefore, the composite membrane material provided in the present application also has the advantage of good cycle stability.
[0078] In some embodiments, based on the total mass of the bridging layer, the mass percentage of the sulfonic acid group is 3.5% to 8.5%.
[0079] In these embodiments, the present application discloses that the mass percentage of the sulfonic acid groups is 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5% or any one of the above two ranges based on the total mass of the bridging layer. In some embodiments, the mass percentage of the β-FeOOH nanorods is 1.5% to 11.5% based on the total mass of the bridging layer.
[0080] The present application discloses in these embodiments that, based on the total mass of the above-mentioned bridging layer, the mass percentage of the above-mentioned β-FeOOH nanorods is any one of 1.5%, 2.0%, 3.0%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 7.5%, 8.0%, 8.5%, 9.0%, 9.5%, 11.5% or any one of the values satisfying any two of the above ranges.
[0081] In some embodiments, the polymer includes structural units derived from 2-acrylamide-2-methylpropane sulfonic acid or its salt monomers.
[0082] In some embodiments, the 2-acrylamide-2-methylpropane sulfonic acid or salt thereof monomer includes any one or more of 2-acrylamide-2-methylpropane sulfonic acid and alkali metal salts of 2-acrylamide-2-methylpropane sulfonic acid.
[0083] The CAS number of 2-acrylamide-2-methylpropane sulfonic acid (AMPS) in this application is 15214-89-8, and the molecular formula is C 7 H 13 NO 4 S, molecular weight is 207.24.
[0084] In some embodiments, the polymer includes structural units derived from vinylbenzenesulfonic acid or its salt monomers.
[0085] In some embodiments, the vinylbenzenesulfonic acid or its salt monomer includes any one or more of vinylbenzenesulfonic acid and alkali metal salts of vinylbenzenesulfonic acid. In the present application, the alkali metal salt of vinylbenzenesulfonic acid includes any one or more of sodium vinylbenzenesulfonate and potassium vinylbenzenesulfonate.
[0086] The CAS number of the sodium vinylbenzene sulfonate of the present application is 60081-73-4, and the molecular formula is C 8 H 7 NaO 2 S, molecular weight is 190.19.
[0087] In some embodiments, the weight average molecular weight of the polymer is 300-100,000.
[0088] The polymer PAMPS formed by 2-acrylamide-2-methylpropane sulfonic acid (AMPS) in the present application serves as a bridging layer to facilitate the attachment of β-FeOOH nanorods.
[0089] The polymer sodium polyvinylbenzenesulfonate formed by sodium vinylbenzenesulfonate in the present application serves as a bridging layer to facilitate the attachment of β-FeOOH nanorods.
[0090] The weight average molecular weight of the present application refers to the sum of the products of the weight fractions of molecules of different molecular weights in the polymer and their corresponding molecular weights. The weight average molecular weight of the polymer of the present application can be tested by methods known in the art, such as gel chromatography, and the specific test standards can refer to the conventional standards in the art.
[0091] In these embodiments, the present application discloses that the weight average molecular weight of the above polymer is any one of 300, 400, 500, 600, 700, 800, 900, 1000, 2000, 5000, 8000, 10000, 50000, 100000 or any one of the values satisfying any two of the above ranges.
[0092] In some embodiments, the aspect ratio of the β-FeOOH nanorods is 40-60:1.
[0093] In the present application, aspect ratio refers to the ratio between the length and diameter of a one-dimensional nanorod, wherein the length of a one-dimensional nanorod includes the length of the nanorod structure corresponding to the dimension with a relatively long length compared to the other two-dimensional directions, that is, the length of the third dimension, which includes the distance value between one end and the other end of the nanorod along this dimension. The length of the one-dimensional nanorod can be obtained by photographing. For example, a Lewis acid is photographed using a scanning electron microscope or a scanning transmission electron microscope. Similarly, the diameter of a one-dimensional nanorod includes the size of one of the dimensions in the two-dimensional directions with relatively small sizes. The cross-section of the one-dimensional nanorod can be obtained by photographing, and the diameter of the one-dimensional nanorod can be obtained by calculating the distance value between one end and the other end of the cross-section.
[0094] The present application discloses in these embodiments that the aspect ratio (length / diameter) of the one-dimensional nanorods satisfies any one or more of 40 to 60:1, and the one-dimensional nanorods having this aspect ratio can better exert the oil-water treatment effect.
[0095] In these embodiments, the present application discloses that the aspect ratio of the β-FeOOH nanorods is any one of 40:1, 41:1, 45:1, 47.3:1, 50:1, and 60:1, or any one of the values within any two ranges above.
[0096] In some embodiments, the BET specific surface area of the β-FeOOH nanorods is 75 m 2 / g~105m 2 / g.
[0097] The specific surface area BET in this application refers to the total surface area of the porous material surface, usually expressed in square meters per gram (m 2 / g). It reflects the complexity of the material surface and the characteristics of the pore structure. It is usually measured and calculated by the Brunauer-Emmett-Teller theory. For example, referring to GB / T 19587-2004, the nitrogen adsorption specific surface area analysis test method is used for testing, and the specific surface area of the porous carbon material is calculated by the BET (Brunauer Emmett Teller) method. The test instrument can be the TRISTAR II 3020 specific surface area and porosity analyzer of Micromeritics, USA.
[0098] The present application discloses in these examples that the specific surface area of the β-FeOOH nanorods is 74.8 m 2 / g, 75m 2 / g, 80m 2 / g, 82.5m 2 / g, 85m 2 / g, 85.2m 2 / g, 90m 2 / g, 95m 2 / g、100m 2 / g、105m 2 / g or any of the above two ranges. In some embodiments of the present application, the base film is made by a 3D printing method. Specifically, any conventional 3D printing machine in the art is used for fused deposition modeling (FDM), and a base film bare film model is designed using 3Ds Max software, which provides accurate digital dimensions. The model is imported into a 3D printer, and the thermoplastic filament is extruded onto the printer bed by fused deposition, and then the base film bare film is obtained by post-processing.
[0099] The base membrane prepared by the 3D printing method in the present application has a porous structure, and the holes in the porous structure are arranged neatly and have regular shapes.
[0100] In some embodiments of the present application, the average pore size of the porous structure is 100 μm to 400 μm; the average pore height of the porous structure is 100 μm to 500 μm.
[0101] The present application discloses in these embodiments that the average pore size of the porous structure of the base membrane is any one of 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, 350 μm, 400 μm or any one of the ranges of any two of the above.
[0102] In these embodiments, the present application discloses that the average pore height of the porous structure of the base membrane is any one of 100μm, 150μm, 200μm, 250μm, 300μm, 350μm, 400μm, 450μm, 500μm or any one of the ranges of any two of the above.
[0103] The average pore size in the present application includes the average pore width, and the average pore height refers to the average height of the porous structure, wherein the height direction is consistent with or parallel to the thickness direction of the membrane.
[0104] In some embodiments of the present application, the base film is also plasma treated to further increase the water flux of the base film, wherein the plasma treatment here includes any conventional method in the art, such as using air as the reaction gas, controlling the RF frequency of the plasma treatment equipment to 12MHz~15MHz, the RF power to 6.8W~18W, and the plasma treatment time to 2.5min~3.5min.
[0105] The second aspect of the present application is to provide a method for preparing the composite membrane material described in the first aspect, such as Figure 1A and Figure 1B Schematically, the preparation method includes the following preparation process:
[0106] S100, providing a base film: preparing the base film by a melt deposition method in 3D printing;
[0107] S200, performing surface treatment on the base film to obtain a treated base film;
[0108] S300, placing the treated base film in a monomer solution containing sulfonic acid groups to react to obtain a base film containing a bridging layer;
[0109] S400, placing the base film including the bridging layer in an iron precursor solution, and generating β-FeOOH nanorods on a surface of the bridging layer that is away from the base film.
[0110] In some embodiments, the step of placing the treated base film in a monomer solution containing sulfonic acid groups for reaction comprises:
[0111] adding a monomer solution containing sulfonic acid groups to the irradiation tube;
[0112] placing the treated base film in a monomer solution containing sulfonic acid groups;
[0113] Deoxidation treatment for a period of time;
[0114] Radiation grafting is performed to prepare a base film including a bridging layer.
[0115] In some embodiments, the step of placing the treated base film in a monomer solution containing sulfonic acid groups for reaction comprises:
[0116] A solution of 2-acrylamido-2-methylpropane sulfonic acid (AMPS) dissolved in deionized water was added to the irradiation tube;
[0117] placing the treated basement membrane in the irradiation tube;
[0118] The solution was deoxygenated by purging with nitrogen for 20 min;
[0119] The irradiation tube was sealed and irradiated at a dose rate of 0.59 kGy / h. 60 Co γ-ray irradiation grafting, lasting 17 h;
[0120] Use Soxhlet extraction apparatus for about 8 hours to remove any residual monomer or homopolymer;
[0121] The ABS-g-PAMPS membrane was obtained by washing with deionized water;
[0122] The ABS-g-PAMPS film was dried at 60° C. for 24 h.
[0123] The chemical radiation-induced grafting was chosen in this application mainly to produce uniform active sites, thereby initiating the grafting polymerization process and subsequently firmly attaching the sulfonic acid monomer to the ABS film. In the subsequent mineralization process, the chemically grafted sulfonic acid acts as a bridging agent, and the exposed -SO 3 (-) can chelate with iron ions and serve as nucleation sites. This is conducive to the in-situ growth of β-FeOOH nanorods, enhances the interfacial bonding strength, reduces stripping, and significantly simplifies the mineralization process. The main principles are as follows:
[0124]
[0125] In some embodiments, the step of generating β-FeOOH nanorods comprises:
[0126] providing an iron precursor solution;
[0127] placing the base film including the bridging layer in the iron precursor solution;
[0128] The β-FeOOH nanorods are prepared by heating the reaction in a water bath, the water bath temperature is 50° C. to 80° C., and the water bath time is 12 h to 36 h.
[0129] The present application discloses in these embodiments that the water bath temperature is any one of 50°C, 60°C, 70°C, 80°C or any one of the values within the range of any two of the above.
[0130] The present application discloses in these embodiments that the water bath time is any one of 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h, 25h, 26h, 27h, 28h, 29h, 30h, 31h, 32h, 33h, 34h, 35h, and 36h, or any one of the values satisfying any two ranges thereof.
[0131] In some embodiments, the step of generating β-FeOOH nanorods comprises:
[0132] Add FeCl to 100 mL of aqueous solution 3 6H 2 O is configured to form an iron precursor solution; the concentration of the iron precursor solution is 2g / L to 10g / L;
[0133] placing the base film including the bridging layer in the iron precursor solution;
[0134] The β-FeOOH nanorods were obtained by heating the reaction in a water bath, the water bath temperature was 60°C, and the water bath time was 24 h.
[0135] In some embodiments, the step of surface treating the base film comprises:
[0136] The base film is ultrasonically cleaned to remove surface contaminants;
[0137] Place the base film in an etching solution at 40°C to 80°C for 10min to 30min;
[0138] After the treatment is completed, take it out, wash it with deionized water, and then dry it.
[0139] In some embodiments, the etching solution includes an acidic solution of potassium permanganate or a sodium hydroxide solution.
[0140] This application uses an acidic solution of potassium permanganate as an example for explanation in the subsequent embodiments. The configuration process of the acidic solution of potassium permanganate is as follows:
[0141] KMnO 4 Dissolve in 100 mL of deionized water to form a 6 g / L solution, then add 2 mL of 10.2 M sulfuric acid (H 2 SO 4 ) and 3.6 mL 4.2 M phosphoric acid (H 3 PO 4 ), mix well to obtain an acidic solution of potassium permanganate.
[0142] In the present application, the base film is placed in an etching solution at any one of 40° C., 50° C., 60° C., 70° C., and 80° C. for any one of 10 min, 20 min, and 30 min.
[0143] In the present application, the base film is treated in an etching solution, which can increase the roughness of the base film, but the membrane pore size of the base film does not change significantly. The base film with increased roughness is conducive to the subsequent attachment of β-FeOOH nanorods to the membrane surface.
[0144] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0145] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0146] Conventional techniques of inorganic chemistry within the art can be used in this application. In the following examples, efforts are made to ensure the accuracy of the numbers used (including amounts, temperatures, reaction times, etc.), but some experimental errors and deviations should be considered. The temperatures (in degrees Celsius) used in the following examples are expressed in ° C, and the pressure is atmospheric pressure or near atmospheric pressure. All pharmaceutical reagents are purchased at AR grade, and all reactions are carried out under argon protection. Unless otherwise noted, all reagents are obtained from commercial channels.
[0147] Example 1-1
[0148] A method for preparing a photocatalytic composite film material is provided, the preparation method comprising:
[0149] S100, providing base film: an industrial-grade 3D printer (F170, Stratasys, USA) uses the melt deposition technology to print out an ABS base film with uniform and regular membrane pores according to the designed coordinates. The thickness of the base film is 254 μm. The acrylonitrile-butadiene-styrene (ABS) copolymer used has a CAS number of 9003-56-9 and a molecular formula of C 15 H 17 N, molecular weight is 211.30218, the molar ratio of each monomer in acrylonitrile-butadiene-styrene copolymer is: acrylonitrile: butadiene: styrene = 1:1:2, and the accuracy of the 3D printer is set to 0.005 inches. Since the printed model needs to be melt-deposited on the soluble support material, it is immersed in a sodium hydroxide solution at a temperature of 60°C and a pH of 12 for 5 minutes until the model can be easily peeled off. The ABS base film with a pore size of 170μm×330μm is printed.
[0150] S210, ultrasonically cleaning the ABS base film to remove surface pollutants;
[0151] S220, prepare the acidic solution of potassium permanganate: add 6g / L KMnO 4 To the solution, add 2 mL of 10.2 M sulfuric acid (H 2 SO 4 ) and 3.6 mL 4.2 M phosphoric acid (H 3 PO 4 ), mix well to obtain an acidic solution of potassium permanganate.
[0152] S230, placing the ABS base film after ultrasonic cleaning in an acidic solution of potassium permanganate and treating it at room temperature for 20 minutes to obtain a treated base film;
[0153] S300, adding a 2-acrylamide-2-methylpropane sulfonic acid (AMPS) solution dissolved in deionized water to the irradiation tube; placing the treated basement membrane in the irradiation tube; purging with nitrogen for 20 minutes to deoxygenate the solution; sealing the irradiation tube and irradiating at a dose rate of 0.59 kGy / h. 60 Coγ-ray irradiation grafting lasts for 17 hours; using a Soxhlet extraction apparatus for about 8 hours to remove any residual monomers or homopolymers; washing with deionized water to obtain an ABS-g-PAMPS membrane; and drying the above ABS-g-PAMPS membrane at 60°C for 24 hours, wherein the weight average molecular weight of the PAMPS membrane is 50,000.
[0154] S410, add FeCl to 100mL aqueous solution 3 6H 2 O is configured to form an iron precursor solution; the concentration of the iron precursor solution is 6g / L;
[0155] S420, placing the base film including the bridging layer in the iron precursor solution;
[0156] S430, heating the reaction in a water bath to obtain β-FeOOH nanorods, the water bath temperature is 60° C., and the water bath time is 24 h.
[0157] The composite film material is placed in a scanning electron microscope. The specific testing process includes spraying gold to prepare the sample, and then placing it in the sample chamber of the scanning electron microscope to obtain a scanning electron microscope spectrum, such as Figure 2A Hint.
[0158] Example 1-2
[0159] A method for preparing a photocatalytic composite film material is provided, and the method for preparing the photocatalytic composite film material includes the following differences from Example 1-1: in step S410, the concentration of the iron precursor solution is 2 g / L;
[0160] Other aspects remain the same as those of Example 1-1.
[0161] The composite membrane material containing the bridging layer prepared in this example was placed in a scanning electron microscope to obtain a scanning electron microscope spectrum, and the Figure 2B .
[0162] Examples 1-3
[0163] A method for preparing a photocatalytic composite film material is provided, and the method for preparing the photocatalytic composite film material includes the following differences from Example 1-1: in step S410, the concentration of the iron precursor solution is 4 g / L;
[0164] Other aspects remain the same as Example 1-1.
[0165] The composite membrane material containing the bridging layer prepared in this example was placed in a scanning electron microscope to obtain a scanning electron microscope spectrum, and the Figure 2C .
[0166] Examples 1-4
[0167] A method for preparing a photocatalytic composite film material is provided, and the method for preparing the photocatalytic composite film material includes the following differences from Example 1-1: in step S410, the concentration of the iron precursor solution is 8 g / L;
[0168] Other aspects remain the same as Example 1-1.
[0169] The composite membrane material containing the bridging layer prepared in this example was placed in a scanning electron microscope to obtain a scanning electron microscope spectrum, and the Figure 2D .
[0170] Examples 1-5
[0171] A method for preparing a photocatalytic composite film material is provided, and the method for preparing the photocatalytic composite film material includes the following differences from Example 1-1: in step S410, the concentration of the iron precursor solution is 10 g / L;
[0172] Other aspects remain the same as Example 1-1.
[0173] The composite membrane material containing the bridging layer prepared in this example was placed in a scanning electron microscope to obtain a scanning electron microscope spectrum, and the Figure 2E .
[0174] Comparative Example 1
[0175] An ABS base film is provided. The ABS base film is the ABS base film prepared in Example 1-1, and no bridging layer is formed on the surface of the ABS base film, and no β-FeOOH nanorods are generated.
[0176] The ABS base film of this embodiment was placed in a scanning electron microscope to obtain a scanning electron microscope spectrum. Figure 2F .
[0177] Combination FIG. 2A to FIG. 2F It can be seen that with the increase of mineralization solution concentration, the amount of goethite on the membrane surface increased significantly and was evenly dispersed on the membrane surface. When the concentration of the mineralization solution reached 10 g / L, goethite agglomeration occurred on the membrane surface.
[0178] Comparative Example 2
[0179] A method for preparing a photocatalytic composite film material is provided, and the method for preparing the photocatalytic composite film material is different from that of Example 1-1 in that:
[0180] S300, adding a solution of methacrylic acid sulfobetaine dissolved in deionized water to the irradiation tube; placing the treated basement membrane in the irradiation tube; purging with nitrogen for 20 minutes to deoxygenate the solution; sealing the irradiation tube and irradiating at a dose rate of 0.59 kGy / h. 60 Coγ-ray irradiation grafting lasts for 17 hours; using a Soxhlet extraction apparatus for about 8 hours to remove any residual monomers or homopolymers; washing with deionized water to obtain a composite membrane; drying the above composite membrane at 60°C for 24 hours, and the weight average molecular weight of the methacrylic acid sulfobetaine polymer formed in the composite membrane is 87,000.
[0181] The composition and some performance parameters of the composite membranes obtained in the above embodiments and comparative examples are as follows:
[0182] Table 1 Performance list
[0183]
[0184] Example 2-1
[0185] A method for preparing a composite membrane material including a bridging layer is provided, and the method is different from that of Example 1-1 in that, during the preparation of the ABS base membrane, the membrane pore size process parameters are adjusted to print an ABS base membrane with a pore size of 240 μm×400 μm. Other aspects are the same as those of Example 1-1.
[0186] Example 3-1
[0187] A preparation method of a composite membrane material including a bridging layer is provided, and the preparation method is different from Example 1-1 in that: after the ABS base membrane is prepared, the ABS base membrane with a certain aperture is used to prepare a corresponding plasma-modified 3D printed ABS separation membrane according to the following steps: cleaning and drying the base membrane; the prepared ABS base membrane is fully cleaned with pure water, and then dried to remove moisture, and specifically, it can also be placed in an oven at 60°C to dry, to obtain a pre-treated ABS base membrane. Plasma treatment of the base membrane; using plasma surface treatment equipment, specifically Harrick plasma cleaning machine PDC-32G-2, in a vacuum state, the base membrane is plasma treated with air as a reaction gas to form a nanostructure layer on the surface of the base membrane; wherein the radio frequency frequency is 13.56MHz, and the radio frequency power is 18W.
[0188] Other aspects remain the same as Example 1-1.
[0189] Example 4-1
[0190] A method for preparing a composite membrane material comprising a bridging layer is provided, the preparation method being different from that of Example 1-1 in that, in step S300, the monomer 2-acrylamide-2-methylpropane sulfonic acid (AMPS) is replaced by the monomer sodium vinylbenzene sulfonate, and the weight-average molecular weight of the formed polymer is 55,000, and the mass percentage of the sulfonic acid group based on the total mass of the polymer bridging layer is 6.5%, and other aspects remain the same as those of Example 1-1.
[0191] Test Case
[0192] (1) Testing the water contact angle of the films obtained in the above embodiments and comparative examples:
[0193] The measuring instrument is a contact angle meter produced by Kino Corporation of the United States. The specific testing process is to cut each film into small pieces, paste them on a glass slide, and place them on a water contact angle machine for direct measurement.
[0194] The test results are shown in Table 2, and the test drawings of Example 1 and Comparative Example 1 are shown in Table 2. Figure 3A Hint.
[0195] (2) Testing the underwater oil contact angles of the films obtained in the above embodiments and comparative examples:
[0196] The measuring instrument is a contact angle meter produced by Kino Corporation of the United States. The specific testing process is to cut each membrane into small pieces, paste them on a glass slide and put them into fiberglass. Water is added to the fiberglass and diiodomethane is used as the oil for direct measurement.
[0197] The test results are shown in Table 2, and the test drawings of Example 1 and Comparative Example 1 are shown in Table 2. Figure 3B Hint.
[0198] (3) Testing the water flux and retention rate of the membranes obtained in the above embodiments and comparative examples:
[0199] The flux was measured by injecting 25 mL of deionized water into the micro-filter cup and recording the time it takes for the water to penetrate through the membrane pores to the bottom of the beaker.
[0200] The retention rate is calculated by weighing the initial weight of the oil (m 1 ) and the initial weight of the device (m 2 ) and record it, pour it into the device, record the weight of the device and the oil (m 3 ), record the ratio of the weight of the device and the oil to the initial weight of the oil and the initial weight of the device, using diiodomethane as the oil.
[0201] The test results are shown in Table 2, and the test drawings of Example 1 and Comparative Example 1 are shown in Table 2. Figure 4A Hint.
[0202] (4) Testing the separation effect of the membranes prepared in the above-mentioned Example 1 and Comparative Example 1 on oil-water mixture: The testing method is the same as above, and the oil includes n-hexane, n-heptane, petroleum ether, gasoline, and soybean oil. The volume ratio between each oil and each water is 1:1.
[0203] The test results are shown in Table 3, and the test drawings of Example 1 and Comparative Example 1 are shown in Table 3. FIG. 4B to FIG. 4F Hint.
[0204] (5) Testing the cyclic stability of the membranes prepared in the above-mentioned Examples 1-1 after treating the oil-water mixture multiple times:
[0205] The flux was measured by injecting 25 mL of deionized water into the micro-filter cup, recording the time it took for the water to penetrate through the membrane pores to the bottom of the beaker, and then weighing the initial weight of the oil (m 1 ) and the initial weight of the device (m 2) and record it, pour it into the device, record the weight of the device and the oil (m 3 ), record the ratio of the weight of the device and oil to the initial weight of the oil and the initial weight of the device.
[0206] After briefly flushing the membrane, the above experiment was repeated until the separation efficiency of the membrane changed.
[0207] The test results are shown in Table 4, and the test drawings are shown in Figure 5 Hint.
[0208] (6) Testing the photo-Fenton reaction process of the films obtained in the above-mentioned Examples 1-1:
[0209] A beaker and a xenon lamp (350W) with a light intensity of 200mW / cm 2 , and a xenon lamp equipped with a 420 nm cut-off filter was used as the light source. Before light irradiation, the membrane was immersed in 100 mL of dye solution (5 ppm) and kept in the dark for 30 min to reach adsorption-desorption equilibrium. The initial dye concentration (C 0 ) was measured using a Hitachi U-3010 spectrophotometer. Subsequently, at timed intervals, the bare ABS film and the β-FeOOH@ABS film were measured after adding 1 mL of H 2 O 2 The residual dye concentration after t ), and set a setting that does not add H 2 O 2 of control conditions.
[0210] The test results of Example 1-1 are as follows Figure 6 Hint.
[0211] Table 2 Performance list
[0212]
[0213] Table 3 Performance list
[0214]
[0215] Table 4 Performance list
[0216]
[0217] In summary, the design method provided in the present application can ensure the stability of the recycling of the membrane itself while having good oil-water separation efficiency.
[0218] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A photocatalytic composite film material, characterized in that: include: Base film: comprising acrylonitrile-butadiene-styrene copolymer; A bridging layer is located on one side of the base film; the bridging layer includes a polymer, and the polymer includes a sulfonic acid group; β-FeOOH nanorods: connected to the sulfonic acid groups.
2. The composite membrane material according to claim 1, characterized in that: Based on the total mass of the bridging layer, the mass percentage of the sulfonic acid group is 3.5% to 8.5%; and / or; Based on the total mass of the bridging layer, the mass percentage of the β-FeOOH nanorods is 1.5% to 11.5%.
3. The composite membrane material according to any one of claims 1 to 2, characterized in that: The polymer includes structural units derived from 2-acrylamide-2-methylpropane sulfonic acid or its salt monomers; and / or; The weight average molecular weight of the polymer is 300 to 100,000.
4. The composite membrane material according to any one of claims 1 to 2, characterized in that: The aspect ratio of the β-FeOOH nanorods is 40 to 60:1; and / or; The specific surface area of the β-FeOOH nanorods is 75 m 2 / g~105m 2 / g.
5. The composite membrane material according to any one of claims 1 to 2, characterized in that: The base film is made by 3D printing method; The base film has a porous structure, and the average pore size of the porous structure is 100 μm to 400 μm; The average pore height of the porous structure is 100 μm to 500 μm.
6. A method for preparing the composite membrane material according to claim 1, characterized in that: The preparation process includes the following: Providing a base film: the base film is prepared by a melt deposition method in 3D printing; The base film is subjected to surface treatment to obtain a treated base film; placing the treated base film in a monomer solution containing sulfonic acid groups to react to obtain a base film containing a bridging layer; The base film including the bridging layer is placed in an iron precursor solution, and β-FeOOH nanorods are generated on a surface of the bridging layer that is away from the base film.
7. The preparation method according to claim 6, characterized in that: The step of placing the treated base film in a monomer solution containing sulfonic acid groups for reaction comprises: adding a monomer solution containing sulfonic acid groups to the irradiation tube; placing the treated base film in a monomer solution containing sulfonic acid groups; Deoxidation treatment for a period of time; Radiation grafting is performed to prepare a base film including a bridging layer.
8. The preparation method according to any one of claims 6 to 7, characterized in that: The step of generating β-FeOOH nanorods comprises: providing an iron precursor solution; placing the base film including the bridging layer in the iron precursor solution; The β-FeOOH nanorods are prepared by heating the reaction in a water bath, the water bath temperature is 50° C. to 80° C., and the water bath time is 12 h to 36 h.
9. The preparation method according to any one of claims 6 to 7, characterized in that: The step of surface treating the base film comprises: Ultrasonic cleaning of the basement membrane to remove surface contaminants; The base film is placed in an etching solution at 40°C to 80°C for 10min to 30min; After the treatment is completed, take it out, wash it with deionized water, and then dry it.
10. Application of a photocatalytic composite membrane material in the field of oil-water separation, characterized in that: The composite membrane is the composite membrane material according to any one of claims 1 to 5 or the composite membrane material prepared by the preparation method according to any one of claims 6 to 9.